Determinan Partisipasi Kerja Perempuan dalam Sektor Informal di Indonesia Tahun 2019 - Anindya Tyas Wandaweka; Dewi Purwanti (Seminar Nasional Official Statistics, 2021)
A conducive labor market can encourage women's interest to actively participate in the economy. However, in 2019, women tend to work in the informal sector rather than the formal sector, even though work in the informal sector has high work risks, minimal protection, and low benefits. Using Sakernas August data for 2019, this study aims to describe the characteristics of women in formal and informal sector work in Indonesia in 2019, examine the variables that influence them, and determine the tendency of the variables that influence them. The method used in this study is binary logistic regression. The results of the study show that women in Indonesia who are elderly, have low education levels, have never attended job training, have been married and living in rural areas have a greater tendency to work in the informal sector.